Magnetic excitations of the classical spin liquid MgCr2O4 - Bai, X; Paddison, JAM; Kapit, E; Koohpayeh, SM; Wen, J-J; Dutton, SE; Savici, AT; Kolesnikov, AI; Granroth, GE; Broholm, CL; Chalker, JT; Mourigal, M (American Physical Society, 2019)
We report a comprehensive inelastic neutron-scattering study of the frustrated pyrochlore antiferromagnet MgCr2O4 in its cooperative paramagnetic regime. Theoretical modeling yields a microscopic Heisenberg model with exchange interactions up to third-nearest neighbors, which quantitatively explains all the details of the dynamic magnetic response. Our work demonstrates that the magnetic excitations in paramagnetic MgCr2O4 are faithfully represented in the entire Brillouin zone by a theory of magnons propagating in a highly-correlated paramagnetic background. Our results also suggest that MgCr2O4 is proximate to a spiral spin-liquid phase distinct from the Coulomb phase, which has implications for the magneto-structural phase transition in MgCr2O4.